Strongyloidiasis Current Status with Emphasis in Diagnosis and Drug Research - Tiago Mendes; Karen Minori; Marlene Ueta; Danilo Ciccone Miguel; Silmara Marques Allegretti (Journal of Parasitology Research)
Strongyloidiasis is a parasitic neglected disease caused by the nematode Strongyloides stercoralis affecting 30 to 100 million people worldwide. Complications, strongly associated with alcoholism, organ transplants, and HTLV-1 virus, often arise due to late diagnosis, frequently leading to patient death. Lack of preemptive diagnosis is not the only difficulty when dealing with this parasite, since there are no gold standard diagnostic techniques, and the ones used have problems associated with sensitivity, resulting in false negatives. Treatment is also an issue as ivermectin and benzimidazoles administration leads to inconsistent cure rates and several side effects. Researching new anti-Strongyloides drugs is a difficult task since S. stercoralis does not develop until the adult stages in Mus musculus (with the exception of SCID mice), the main experimental host model. Fortunately, alternative parasite models can be used, namely, Strongyloides ratti and S. venezuelensis. However, even with these models, there are other complications in finding new drugs, which are associated with specific in vitro assay protocol steps, such as larvae decontamination. In this review, we highlight the challenges associated with new drug search, the compounds tested, and a list of published in vitro assay methodologies. We also point out advances being made in strongyloidiasis diagnosis so far.